When two are better than one: bright phosphorescence from non-stereogenic dinuclear iridium(iii) complexes. Issue 16 (17th March 2016) - Daniels, Ruth E.; Culham, Stacey; Hunter, Michael; Durrant, Marcus C.; Probert, Michael R.; Clegg, William; Williams, J. A. Gareth; Kozhevnikov, Valery N.
Abstract : Tridentate N^C^N-coordinating ligands in combination with bis-N^C-bridging ligands give rise to achiral dinuclear iridium complexes displaying exceptionally high radiative rate constants. Abstract : A new family of eight dinuclear iridium(iii ) complexes has been prepared, featuring 4, 6-diarylpyrimidinesL y as bis-N^C-coordinating bridging ligands. The metal ions are also coordinated by a terminal N^C^N-cyclometallating ligandL X based on 1, 3-di(2-pyridyl)benzene, and by a monodentate chloride or cyanide. The general formula of the compounds is IrL X Z 2 L y (Z = Cl or CN). The family comprises examples with three differentL X ligands and five different diarylpyrimidinesL y, of which four are diphenylpyrimidines and one is a dithienylpyrimidine. The requisite proligands have been synthesised via standard cross-coupling methodology. The synthesis of the complexes involves a two-step procedure, in whichL X H is reacted with IrCl3 ·3H2 O to form dinuclear complexes of the form [IrL X Cl(μ-Cl)]2, followed by treatment with the diarylpyrimidineL y H 2 . Crucially, each complex is formed as a single compound only: the strong trans influence of the metallated rings dictates the relative disposition of the ligands, whilst the use of symmetrically substituted tridentate ligands eliminates the possibility of Λ and Δ enantiomers that are obtained when bis-bidentate units are linked through bridging ligands. The crystal structure of one member of the family has been obtained using a synchrotron X-ray source. All of the complexes are very brightly luminescent, with emission maxima in solution varying over the range 517–572 nm, according to the identity of the ligands. The highest-energy emitter is the cyanide derivative whilst the lowest is the complex with the dithienylpyrimidine. The trends in both the absorption and emission energies as a function of ligand substituent have been rationalised accurately with the aid of TD-DFT calculations. The lowest-excited singlet and triplet levels correlate with the trend in the HOMO–LUMO gap. All the complexes have quantum yields that are close to unity and phosphorescence lifetimes – of the order of 500 ns – that are unusually short for complexes of such brightness. These impressive properties stem from an unusually high rate of radiative decay, possibly due to spin–orbit coupling pathways being facilitated by the second metal ion, and to low non-radiative decay rates that may be related to the rigidity of the dinuclear scaffold.